Heat knockdown resistance and chill-coma recovery as correlated responses to selection on mating success at high temperature in Drosophila buzzatii - Stazione, Leonel Daniel (2020)
Reproduction and related traits such as mating success are strongly affected by thermal stress. We tested direct and correlated responses to artificial selection in replicated lines of Drosophila buzzatii that were selected for mating success at high temperature. Knockdown resistance at high temperature (KRHT) and chill-coma recovery (CCR) were tested as correlated selection responses. Virgin flies were allowed to mate for four hours at 33°C in three replicated lines (S lines) to obtain the selected flies and then returned at 25°C to lay eggs. Other three replicated lines were maintained at 25°C without any selection as control (C lines). After 15 selection generations, KRHT and CCR were measured. Both traits were assessed in flies that did not receive any hardening pretreatments as well as in flies that were either heat or cold hardened. Thermotolerance traits showed significant correlated responses with higher KRHT in S than in C lines, both with a heat-hardening pretreatment and without a heat-hardening pretreatment. CCR time was longer in S than in C lines both with a cold-hardening pretreatment and without a cold-hardening pretreatment. Hardening treatments improved both KRHT and CCR in all cases excepting KRHT in C lines. Overall, KRHT and CCR showed an antagonistic pattern of correlated responses to our selection regime, suggesting either pleiotropy or tightly linked trait-specific genes partially affecting KRHT and CCR.